Zero-Burning Policy in Land Preparation: Social Changes and Its Impact on Communities and the Environment - Ekawati, Sulistya; Siburian, Robert; Surati, Surati; Nurlia, Ari; Yanarita, Yanarita; Sundary, Letsu Vella (Forestry Faculty, Universitas Hasanuddin, 2024)
In Indonesia, forest and land fires have become an annual occurrence, with devastating effects. Following major fires in 2015, the government implemented policies restricting the use of fire in land preparation. This policy has affected the livelihoods of traditional farmers who still use fire for land clearing. The research aims to analyze the social changes that have occurred among traditional farmers as a result of the policy to ban burning in land preparation, and to assess its impact. The study was undertaken in Pulang Pisau Regency (Central Kalimantan) and Ogan Komering Ilir Regency (South Sumatera). Findings reveal two types of social transformation processes, namely, changes in agricultural commodities and changes in livelihoods. In general, fire policy restrictions in land preparation improved peatland ecosystems, but has had a detrimental impact on some rural communities living around peatlands. To anticipate these effects, the government promoted no-burn land preparation techniques and initiated a new paddy field construction scheme. However, both were less successful due to local resistance for their unsuitability in the local context.